Analysis of the Influence of the Relative Position of Retarders and Bypass Tracks on the Length of the Neck of the Sorting Slide and Their Automated Design - Berezovyi, M. I.; Bozhko, M. P.; Malashkin, V. V.; Bolvanovska, T. V.; Mazurenko О. O. (Science and Transport Progress, 2025)
Purpose. The purpose of this study is to find ways to reduce the length of sorting yard humps by analyzing the relative positioning of the decelerators on the descent section and other elements of the track layout of the humps, such as turnouts, their isolated pre-switch sections, curved track sections and adjacent tracks, including bypass tracks. Methodology. One of the approaches to reducing energy consumption during the breaking up and formation of trains on classification humps is the improvement of their track layout design, in particular the development and implementation of measures to reduce the length of hump throats. To solve the problem, a comprehensive analysis of the technology of dissolving trains on sorting humps was used, methods of scientific analysis and synthesis of track development design based on analytical geometry were applied, as well as simulation modelling methods to determine the mutual position of the decelerators of the descent section and adjacent bypass tracks. Findings. Based on an analysis of the lower clearance limits for structures (profile «C») and the dimensional characteristics of beam-type pneumatic wagon retarders, technical solutions were developed to allow a track from the outer group of classification tracks to approach the retarder pit area bypassing the hump body. The calculation of the parameters for connecting a bypass track from the group of classification tracks showed that the straight section of track behind the braking position can be reduced on average by 5.65 meters, depending on the type of lower retarder installed at the given braking point. Originality. The work improves the methods for designing the descent section of sorting humps and bypass tracks; for the first time, it establishes the dependence of the reduction in the length of the switch throat of the end track bundle of the sorting yard on the types of retarders with which the braking position is equipped. Practical value. The practical value of the study lies in the potential application of the obtained solutions by design engineers during reconstruction works on existing classification humps and in the design of new hump classification facilities on mainline railways and industrial railway systems.